SEBARAN KERAMIK ASING PADA MASA SRIWIJAYA (ABAD KE-7-13 MASEHI) DI PESISIR TIMUR SUMATERA BAGIAN SELATAN: BUKTI KRONOLOGI DAN HUBUNGAN INTERNASIONAL - Eka Asih Putrina Taim (Balai Arkeologi Bali, 2020)
Srivijaya is the largest maritime kingdom in Southeast Asia, trade is one of the main elements that makes it famous. The traces of his greatness are spread not only in South Sumatra but also in neighboring countries. Ceramics are one of the most archaeological remains found in various archaeological sites during the Srivijaya period in southern Sumatra. These fragments can be found in various characteristics of the site, from settlements to religions, and are a strong indication of past activity. Ceramic findings can lead us to explore not only the shape and decoration but also the origin of the object produced and the relative chronology of each of these ceramics. Further benefits of the findings of foreign ceramics, can be traced from past activities to international trade relations and even political. This article will discuss the findings of foreign ceramics in the South Sumatra region and the background of its existence in the past, especially in the Sriwijaya era. Qualitative method is a method used to discuss these problems, namely by analyzing the shape, origin and chronology of ceramics, and the relationship of their existence at each site. Aim of this article give an idea of the distribution of ancient ceramics especially from Cina which were in the archaeological sites of the Srivijaya period in South Sumatra in the 7th to 13th centuries AD (Sriwijaya era). The result of the research is an illustration of the distribution of types of Chinese ceramic findings found in Sriwijaya period sites based on shape and chronology so that their function and role can be determined. Sriwijaya merupakan kerajaan maritim terbesar di Asia Tenggara. Perdagangan merupakan salah satu unsur utama yang membuatnya terkenal. Keramik salah satu artefak yang paling banyak ditemukan diberbagai situs masa Sriwijaya di Sumatera bagian selatan. Fragmen keramik tersebut ditemukan diberbagai karakteristik situs, dari permukiman hingga keagamaan, dan merupakan salah satu indikasi kuat aktivitas masa lalu. Temuan keramik juga dapat mengetahui dimana diproduksi dan kronologi relatifnya. Manfaat lebih lanjut dari temuan keramik asing, dapat melacak aktivitas masa lalu hingga hubungan perdagangan internasional bahkan politis. Artikel ini akan membahas mengenai temuan keramik di wilayah Sumatera Selatan dan hal-hal yang melatarbelakangi keberadaanya di masa lalu terutama di masa Sriwijaya. Metode yang digunakan metode kualitatif dengan menganalisa bentuk, asal dan kronologi keramik serta hubungan keberadaannya pada tiap situs. Tujuan artikel ini memberikan gambaran tentang persebaran keramik kuno terutama dari Cina yang berada di Situs-situs arkeologi masa Sriwijaya di Sumatera Selatan pada abad ke-7 hingga abad ke-13 Masehi (masa Sriwijaya). Hasil penelitian berupa gambaran mengenai sebaran jenis temuan keramik Cina yang ditemukan di Situs-situs masa Sriwijaya berdasarkan bentuk dan kronologi sehingga dapat diketahui fungsi dan peranannya.